2004
DOI: 10.4321/s1130-01082004001100003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of argon plasma coagulation for the treatment of hemorrhagic radiation proctitis

Abstract: Objective: to evaluate the efficacy, safety and medium-/longterm clinical course of patients undergoing endoscopic treatment with argon plasma coagulation for hemorrhagic radiation proctopathy.Design: descriptive, retrospective study with medium-and long-term follow-up.Patients, material and methods: ten patients were treated with argon plasma coagulation for hemorrhagic radiation proctopathy between July 1998 and February 2003. Inclusion criteria were: evidence of chronic rectal bleeding, consistent endoscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…Women may present with CRP after radiotherapy for local control of gynecological cancers (cervical, ovarian); however, in most Western populations, they constitute a small minority. 6 Unlike our study, others have enrolled a higher proportion of female patients, 1,7,12,13 and therefore caution should be exercised in the interpretation and comparison of these studies because the technique and dose of radiotherapy differ significantly among different malignancies. Consequently, differences in demographics may contribute to the overall efficacy and complications of all treatments, including APC therapy, for radiation proctitis.…”
Section: Discussionmentioning
confidence: 73%
“…Women may present with CRP after radiotherapy for local control of gynecological cancers (cervical, ovarian); however, in most Western populations, they constitute a small minority. 6 Unlike our study, others have enrolled a higher proportion of female patients, 1,7,12,13 and therefore caution should be exercised in the interpretation and comparison of these studies because the technique and dose of radiotherapy differ significantly among different malignancies. Consequently, differences in demographics may contribute to the overall efficacy and complications of all treatments, including APC therapy, for radiation proctitis.…”
Section: Discussionmentioning
confidence: 73%
“…Single sessions have been reported to significantly improve symptoms [62], but on average, two to three treatments are needed to achieve this result. Improvements persisted for a number of months after therapy was finished [2, 63]. Most of the complications reported were mild and included cramps, mucus discharge, and stricture [2].…”
Section: Treatmentsmentioning
confidence: 99%
“…The most appropriate treatment is still not clear, especially in the absence of a scoring system [3,6]. Nonsurgical management is preferable to surgery, as the latter is associated with high morbidity and mortality and should be reserved for intractable cases [1,2,4,8,9]. Reports on medical therapy have demonstrated that corticosteroids, nonsteroidal anti-inflammatory drugs (NSAIDs), sucralfate or short-chain fatty acid enemas tend not to be beneficial [1,6,8].…”
mentioning
confidence: 97%
“…with considerable reported side effects [3,4]. In the light of these findings, endoscopic treatment is emerging as an important tool for CRCP management [1,4]. Multiple modalities are available and include Nd:YAG laser, heater probe, bipolar eletrocoagulation (BEC) and argon plasma coagulation (APC) [3,10,11].…”
mentioning
confidence: 99%